Evaluation of 30-day mortality in patients undergoing gastrointestinal endoscopy in a tertiary hospital: a 3-year retrospective survey - Philippe Bichard; Jean-Louis Frossard; Laurent Spahr; Nicolas Goossens; Olivier Chatelanat; Laurent Bochatay; Caroline Bastid (BMJ Open Gastroenterology)
Objective Despite international guidelines recommendations to use mortality as a quality criterion for gastrointestinal (GI) procedures, recent studies reporting these data are lacking. Our objective was to report death causes and rate following GI endoscopies in a tertiary university hospital.Design We retrospectively reviewed all GI procedures made between January 2017 and December 2019 in our tertiary hospital in Switzerland. Data from patients who died within 30 days of the procedure were recorded.Results Of 18 233 procedures, 251 patients died within 30 days following 345 (1.89%) procedures (244/9180 gastroscopies, 53/5826 colonoscopies, 23/2119 endoscopic ultrasound, 19/911 endoscopic retrograde cholangiopancreatography, 6/197 percutaneous endoscopic gastrostomies). Median age was 70 years (IQR 61–79) and 173/251 (68.92%) were male. Median Charlson Comorbidity Index was 5 (IQR 3–7), and 305/345 procedures (88.4%) were undertaken on patients with an ASA score ≥3. Most frequent indications were suspected GI bleeding (162/345; 46.96%) and suspected cancer or tumourous staging (50/345; 14.49%). Major causes of death were oncological progression (72/251; 28.68%), cardiopulmonary failure or cardiac arrest of unkown origin (62/251; 24,7%) and liver failure (20/251; 7.96%). No deaths were caused by complications such as perforation or bleeding.Conclusions Progression of malignancies unrelated to the procedure was the leading cause of short-term death following a GI procedure. After improvements in periprocedural care in the last decades, we should focus on patient selection in this era of new oncological and intensive care therapies. Death rate as a quality criterion is subject to caution as it depends on indication, setting and risk benefit ratio.